2014
DOI: 10.1371/journal.pone.0111983
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Colocalization: Thresholding, Void Voxels and the Hcoef

Abstract: A critical step in the analysis of images is identifying the area of interest e.g. nuclei. When the nuclei are brighter than the remainder of the image an intensity can be chosen to identify the nuclei. Intensity thresholding is complicated by variations in the intensity of individual nuclei and their intensity relative to their surroundings. To compensate thresholds can be based on local rather than global intensities. By testing local thresholding methods we found that the local mean performed poorly while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…Our current simulations, previous work and the equation itself shows that a zero value only occurs when the two molecules never co-occur. This is quite different from a perfect negative correlation where high values for one would be associated with low values for the second and vice versa, together with an intermediate population with more similar values [5]. We have previously demonstrated that populations with perfect negative correlations can have values at the high end of the MOC's range [3,13] and here demonstrate that even a perfect positive correlation plus complete co-occurrence does not always produce a maximal MOC.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Our current simulations, previous work and the equation itself shows that a zero value only occurs when the two molecules never co-occur. This is quite different from a perfect negative correlation where high values for one would be associated with low values for the second and vice versa, together with an intermediate population with more similar values [5]. We have previously demonstrated that populations with perfect negative correlations can have values at the high end of the MOC's range [3,13] and here demonstrate that even a perfect positive correlation plus complete co-occurrence does not always produce a maximal MOC.…”
Section: Discussioncontrasting
confidence: 64%
“…Some coefficients fall outside our bipolar scheme and instead merge the two primary attributes into a single value. These we categorize as hybrids which we suggest includes the Manders Overlap Coefficient (MOC) [2,3] and the H coeff [4,5].…”
mentioning
confidence: 99%
“…Several factors limit the use of current software for visualizing the localization of reporters in biological samples and measuring colocalization 9 12 . One factor is that customization of the software is often required for the equipment, reporters and samples 13 , 14 , and for automated analyses.…”
Section: Introductionmentioning
confidence: 99%
“…However, the inability to automatically select ROIs makes analysis of a large number of images extremely difficult 10 . Background can vary significantly in different portions of the images; therefore, global thresholding to remove background is not a suitable option as discussed by Regeling et al ., as well as Adler and Parmryd 11 , 12 . Different coefficients report colocalisation using a range of 0 to 1 or −1 to 1, which may lead to investigators considering different coefficients significant 8 , 13 .…”
Section: Introductionmentioning
confidence: 89%